ENGLISH LANGUAGE LEARNERSâ MASTERY IN TOEFL STRUCTURE-WRITTEN EXPRESSION (A Case Study at IAIN Antasari, UNLAM, UNISKA and STKIP PGRI in South Kalimantan) - Mufidah, Nida (LET: Linguistics, Literature and English Teaching Journal, 2012)
This research is conducted to find out the mastery of English students department in TOEFL in Structure and written Expression in South Kalimantan of IAIN Antasari Banjarmasin, UNLAM, STKIP PGRI, and UNISKA and to know types of questions in TOEFL which are very difficult and difficult for students to answer. The researcher tested 80 fifth semester students of English Department at IAIN ANTASARI, UNLAM, STKIP PGRI and UNISKA in South Kalimantan on the academic year 2011/2012 , used test distributed to 80 students in the fifth semester The TOEFL prediction test was used to gather the data. Â The result showed the mean score of TOEFL of academic year 2011/2012 classified in beginner category with the mean score 418. The results of TOEFL prediction shows that the mean score of UNLAMâs students is 469, folllowed by IAINâs which is 454, UNISKAâs is 384, while STKIP PGRIâs is 367. Structure and Writen Expression is the most difficult type of questions are relative pronoun, possessive pronoun, personal pronoun and passive voice.